Design method for perovskite absorption layer defect passivation based on density functional theory
By designing the design method based on density general letters, the heterogeneous structure of the solar cell material of the perovskite is constructed and optimized the problem of the easily environmental impact of the perovskite materials, and the effect of improving the efficiency of photoelectric conversion and the stability of the material Essence
Patent Information
- Application Number
- CN202411473145.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-28
AI Technical Summary
Perovskite solar cell materials are easily affected by the environment and lead to structural changes, affecting the photoelectric conversion efficiency, and the existing defect passivation scheme is unsatisfactory.
The design method based on density general letters is used to build and optimize the crystal structure of CSSNCL3, PBSO4, and PBCO3 through the MEDEA and VASP modules to form a heterogeneity structure and perform performance tests to screen the best quality knot combination.
Effectively reduce the structure defects of perovskite, improve the performance of photoelectricity, significantly improve the photoelectric conversion efficiency of the solar cell solar cells, and improve the stability of the material.
Smart Images

Figure CN119380893A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the fields related to computer simulation material calculation and energy material design modification, and in particular to a design method for defect passivation of a perovskite absorption layer based on density functional theory. Background Art
[0002] Perovskite materials have been the focus of research in the energy field for many years due to their unique advantages: high absorption coefficient, long carrier lifetime and high photogenerated carrier transfer rate. However, perovskites with many advantages also have disadvantages that cannot be ignored, that is, they are easily affected by the environment, resulting in structural changes (stability), which further affects the photoelectric conversion efficiency of perovskite solar cells. Such as humidity, heat and ultraviolet light.
[0003] It is well known that growing perovskites at room temperature will lead to more defects. Due to the exposed grain boundary surface, the perovskite structure is extremely sensitive to water (H2O) and oxygen molecules (O) in the environment, leading to the decomposition of the perovskite structure. In order to protect the perovskite film from further degradation, different protective media (including organic molecules, polymers and inorganic nanoparticles) are used to passivate defects to further reduce the impact of structural defects on the stability of perovskite materials. At present, many passivation schemes have been developed to passivate defects in perovskite solar cells (PSCs), but the results obtained are not satisfactory. Therefore, the combination of passivation strategy and passivated materials is particularly important.
[0004] The CsSnCl3 perovskite is surface modified and passivated with PbSO4 and PbCO3 with multifunctional quantum dots. The incorporation of PbSO4 and PbCO3 can effectively modify the perovskite surface by forming strong chemical bonds at the interface, achieving the effects of surface passivation and moisture absorption (H2O), thereby improving the photoelectric conversion efficiency of the device by improving the stability of the perovskite material and the carrier transfer efficiency.
[0005] Due to the differences in the properties of PbSO4, PbCO3 and CsSnCl3, the diversity of structural sections, the complexity of heterojunction combination schemes, and the unpredictable effects in different aspects, if artificial trial and error methods are used for design and adjustment, it will greatly waste manpower and material resources, not only consuming a high time cost, but also difficult to accurately implement micro-control of the structure, and the potential uncertainties and adjustment plans are difficult to predict.
[0006] Therefore, by means of material component simulation, the basic properties of the material can be simulated under certain conditions to simulate the experimental conditions, and the experimental results can be predicted, which will also make it easier to adjust the parameters. This is one of the important application methods in the field of material exploration. Summary of the invention
[0007] The present invention provides a design method for passivation of defects in a perovskite absorption layer based on density functional theory, which is a design method based on density functional theory to reduce structural defects of perovskite and improve photoelectric performance.
[0008] A design method for defect passivation of a perovskite absorption layer based on density functional theory of the present invention is carried out according to the following steps:
[0009] Step 1: Use the VASP module of MedeA to set the lattice parameters of the CsSnCl3 structure according to the experimental values, construct the CsSnCl3 crystal structure, use the PBE functional of the generalized gradient approximation (GGA) to describe the exchange interaction between electrons, and optimize the geometric structure of CsSnCl3 based on the density functional to obtain the CsSnCl3 unit cell with the lowest total energy, that is, in the stable state.
[0010] Step 2. Set the unit cell parameters of PbSO4 and PbCO3 according to the experimental values to construct a crystal structure model. Use the PBE functional of the generalized gradient approximation (GGA) to describe the exchange interaction between electrons. Optimize the geometric structure of PbSO4 and PbCO3 based on density functional to obtain the PbSO4 and PbCO3 unit cells with the lowest total energy, i.e., in the stable state. Use the energy convergence of the crystal structure to determine the parameters for calculation accuracy: k-point, cutoff energy and SCF. Select the appropriate k-point to calculate the bandgap width and band edge position of PbSO4, PbCO3 and CsSnCl3 perovskite materials.
[0011] Step 3: Cut the surface of the PbSO4, PbCO3 and CsSnCl3 selected in step 1 and step 2, and then further optimize the surface structure, combine the optimized components into heterojunctions, adjust the relevant parameters between interfaces, and optimize the heterojunction structure as in step 1. The obtained stable heterojunction structure is tested for performance, and the heterojunction interface parameters are further optimized to screen out the two best (PbSO4, PbCO3) / CsSnCl3 heterojunction structures.
[0012] Step 4. Obtain the final experimental performance values of the (PbSO4, PbCO3) / CsSnCl3 heterojunction through theoretical calculations and perform visual characterization (including electron localization function, state density, band structure, differential charge density, light absorption rate, photoconductivity, and light refractive index), explore the passivation mechanism, and obtain the photoelectric conversion efficiency of the perovskite solar cell with (PbSO4, PbCO3) / CsSnCl3 as the light absorption layer through simulation design calculations.
[0013] Furthermore, the specific contents of constructing the CsSnCl3 crystal structure using MedeA software described in step 1 are: setting the size and space group of the unit cell according to the experimental values, and performing visualization operations.
[0014] Furthermore, the specific contents of using VASP software to optimize the structure of CsSnCl3 in step 1 to obtain a stable CsSnCl3 primitive cell are as follows: setting relevant restriction parameters for the constructed CsSnCl3 crystal structure, using the VASP module of MedeA software to optimize the structure based on the plane wave method density functional theory, and allowing the atomic position, unit cell volume and unit cell shape to be changed according to the interatomic interaction force during the crystal structure optimization process. The PBE functional of the generalized gradient approximation (GGA) is used to describe the exchange interaction of electrons.
[0015] Furthermore, the method of setting the unit cell parameters of PbSO4 and PbCO3 according to experimental values to establish a crystal structure model in step 2 is the same as that in step 1.
[0016] Furthermore, the specific content of selecting appropriate k points to calculate the bandgap width and band edge position of PbSO4, PbCO3 and CsSnCl3 perovskite materials in step 2 is: using different k points to perform self-consistent calculations on the perovskite unit cell until the total energy of the PbSO4, PbCO3 and CsSnCl3 unit cell reaches a minimum value and does not change with the increase of the k point, and then selecting the k point for electronic structure calculation.
[0017] Furthermore, the specific content of selecting a suitable k point to calculate the bandgap width and band edge position of PbSO4, PbCO3 and CsSnCl3 perovskite materials in step 2 is: the band edge position is calculated from the work function and the bandgap width.
[0018] Furthermore, the surface of PbSO4, PbCO3 and CsSnCl3 is cut as described in step three. Specifically, the MedeA software is used to cut the surface of the PbSO4, PbCO3 and CsSnCl3 crystal structures, and the crystal plane with the lowest surface energy is selected as the heterojunction bonding surface, and the structure of the cut surface is optimized as described above to obtain a stable cut surface structure.
[0019] Furthermore, the surfaces of PbSO4, PbCO3 and CsSnCl3 are cut as described in step three, and PbSO4, PbCO3 and CsSnCl3 are combined in sequence to construct a heterojunction structure. Specifically, CsSnCl3 can be cut into two different exposed surfaces in one direction, which are combined with PbSO4 and PbCO3 in sequence to form a heterojunction.
[0020] Furthermore, in step 3, PbSO4, PbCO3 and CsSnCl3 are sequentially combined to construct a heterojunction structure, and the optimal two (PbSO4, PbCO3) / CsSnCl3 heterojunction structures are screened out by designing the surface interface structure and further optimizing the heterojunction interface parameters. Specifically, the constructed (PbSO4, PbCO3) / CsSnCl3 heterojunction band structure can form a type II heterojunction, and the structure with the lowest heterojunction interface binding energy is screened out.
[0021] Furthermore, as described in step three, the PbSO4, PbCO3 and CsSnCl3 obtained in steps one and two are combined in sequence to construct a heterojunction structure, and the specific content of the surface interface structure design is as follows: the preliminary construction of the heterojunction is to use MedeA software to visualize the two cross-sectional structures, stack the cross-sectional surfaces of the geometric model, and construct a rough heterojunction geometric model. This structural model also needs to be optimized-adjust parameters-optimized (the optimized structure is consistent with the above-mentioned optimization content of the monomer crystal structure) to obtain the required stable geometric structure.
[0022] Furthermore, before constructing the heterojunction, the lattice mismatch of the two monomer surfaces at the c-direction interface of the heterojunction structure needs to be calculated. The mismatch formula is as follows:
[0023] Δ=[(|a1-a2| / a1)-1]*100%
[0024] Where Δ represents the lattice mismatch of the monomer crystal structures on both sides of the heterojunction interface;
[0025] a1 represents the lattice constant in the a direction of the upper crystal structure of the heterojunction interface in the heterojunction;
[0026] a2 represents the lattice constant in the a direction of the lower crystal structure of the heterojunction interface in the heterojunction;
[0027] Furthermore, before constructing the heterojunction, the angle mismatch of the two monomer surfaces at the c-direction interface of the heterojunction structure needs to be calculated. The mismatch formula is as follows:
[0028] η=(|γ1-γ2| / γ1)*100%
[0029] Where η represents the angular mismatch of the monomer crystal structures on both sides of the heterojunction interface;
[0030] γ1 represents the lattice angle size in the ab direction of the upper crystal structure of the heterojunction interface in the heterojunction;
[0031] γ2 represents the lattice angle size in the ab direction of the crystal structure under the heterojunction interface in the heterojunction;
[0032] It is worth noting that when constructing a geometric crystal structure model of a heterojunction material, in order to ensure the true reliability of the constructed structure and to ensure the stability of the structure, the mismatch rate must be ≤5%. In order to minimize the mismatch of the crystal lattice during construction, the crystal structure is usually expanded and the appropriate lowest common multiple is selected for expansion.
[0033] When constructing a heterostructure, it is necessary to set The vacuum layers on the left and right are intended to ensure that the heterojunction does not continue in the c direction, making it a separate multilayer structure. More importantly, it is intended to avoid the influence of other interaction forces on the interface structure.
[0034] Furthermore, by combining computer computing power and structural characteristics, specific crystal planes can be selected for crystal vector transformation, which facilitates the construction of heterogeneous structures.
[0035] Furthermore, the final experimental performance values of the (PbSO4, PbCO3) / CsSnCl3 heterojunction are obtained by theoretical calculation as described in step 4 and visualized and specifically characterized, and the specific contents of obtaining the final performance parameters are as follows: the electronic structure, optical and electrical related parameters of the optimized heterojunction structure are calculated using the VASP module based on density functional theory to characterize the related performance of the heterogeneous crystalline structure;
[0036] The electrical performance characterization, wherein the dielectric constant 8 reflects the response degree of the medium to the external electric field, the formula of the dielectric function is as follows;
[0037] ε(ω)=ε1(ω)+iε2(ω) ω is the optical frequency, ε1(ω) and ε2(ω) are the real and imaginary parts of the dielectric function, respectively, the imaginary part represents the absorption behavior and the real part is derived from the imaginary part [ε1(ω) and ε2(ω) are given in detail below].
[0038] Furthermore, electronic structure calculation is to determine the specific band structure and state density information by calculating the Mülliken population number of the system. The principle of optical calculation is to calculate the transition of electrons in the band gap. The calculation formula is as follows:
[0039]
[0040]
[0041]
[0042]
[0043]
[0044] Among them, ε1(ω) and ε2(ω) are the calculation equations for the real and imaginary parts of the dielectric constant, n(ω) is the calculation equation for the refractive index, R(ω) is the calculation equation for the reflectivity, and L(ω) is the extinction coefficient.
[0045] The optical performance characterization, in which the response degree of the structure to light is expressed according to the light absorption coefficient, is derived and calculated by the dielectric function to obtain the absorption spectrum. According to the Lambert-Beer law, a larger absorption coefficient leads to a larger absorption rate. The dielectric function ε and α absorption coefficients are calculated by the following formula:
[0046]
[0047] Among the optical properties, photoconductivity is the key information that can be used to determine the efficiency of the structure in converting photon energy absorbed. The calculation formula of photoconductivity is as follows:
[0048]
[0049] σ0=e 2 n e τ / m* is the DC conductivity, n e is the electron density, τ is the electron relaxation time, m* is the effective electron mass, and the parameter c = [-1, 0] represents the original velocity fraction of the electron after the collision, which is related to the electron localization effect. The real part (Re) of the photoconductivity corresponds to the actual energy consumption, and the imaginary part (Im) represents the conversion of the electric field energy to the electron kinetic energy, based on which it can provide key information on energy changes to reflect the photoelectric conversion efficiency.
[0050] Furthermore, the photoelectric conversion efficiency of the perovskite solar cell with (PbSO4, PbCO3) / CsSnCl3 as the light absorption layer is calculated by simulation design as described in step 4. Specifically, the photoelectric performance parameters of (PbSO4, PbCO3) / CsSnCl3 calculated after optimization are imported into the photovoltaic design platform, and the parameters such as the electrode, charge transfer layer, hole transport layer, light intensity, temperature, interface contact mode, scanning mode and thickness of each functional layer are set in turn according to actual experience values to restore the actual working conditions of PSCs and obtain the photoelectric performance parameters of PSCs.
[0051] Preferably, the energy convergence value in steps 1 and 2 is 1×10 -6 eV, the force converges to The cutoff energy is 450 eV, the k point is sampled in the first Brillouin zone, the sampling points are 6×6×6, and the sampling density is
[0052] Preferably, the density functional theory used in the calculation of the bandgap width and band edge position of PbSO4, PbCO3 and CsSnCl3 in step 2 is HSE06 hybrid density functional theory.
[0053] Preferably, the density functional theory used in the structural optimization calculations described in steps one, two, and three is a PBE hybrid density functional theory.
[0054] Preferably, the band edge position test method described in step 2 is calculated through the work function of the material.
[0055] Preferably, the work function test density functional described in step 2 is a HSE06 hybrid density functional.
[0056] Preferably, the surface interface design described in step three is capable of forming a type II band structure.
[0057] Preferably, the PbSO4 described in step three is a 2×1×x supercell, the PbCO3 is a 2×1×x supercell after crystal vector transformation, and the CsSnCl3 is a 3×1×x supercell.
[0058] Preferably, the PbCO3 in step 3 is obtained by Obtained after the crystal arrow transformation.
[0059] Preferably, the crystal planes with the lowest surface energy described in step 3 are PbSO4(100), PbCO3(001) and CsSnCl3(100) planes.
[0060] Preferably, when the heterojunction combination is performed in step 3, the thickness of the vacuum layer in the vertical direction of the heterojunction interface is
[0061] Preferably, when performing the heterojunction combination described in step 3, the interface mismatch rate between the two interfaces must be ≤5%.
[0062] Preferably, when the heterojunction combination is performed in step 3, the interlayer interface spacing is the spacing of the interatomic forces. within the range.
[0063] Preferably, the (PbSO4, PbCO3) / CsSnCl3 heterojunction structure with stable interface is screened out in step 3, and the two heterojunction structures of PbSO4 / SnCl and PbCO3 / SnCl are more stable.
[0064] Preferably, the photoelectric conversion efficiency of the perovskite solar cell with (PbSO4, PbCO3) / CsSnCl3 as the light absorption layer is obtained by simulation design as described in step 4, and the charge transport layer is SnO2 with a thickness of 20nm.
[0065] Preferably, the photoelectric conversion efficiency of the perovskite solar cell with (PbSO4, PbCO3) / CsSnCl3 as the light absorption layer is obtained by simulation design as described in step 4, and the hole transport layer is Spiro-OMETAD with a thickness of 50nm.
[0066] Preferably, the photoelectric conversion efficiency of the perovskite solar cell with (PbSO4, PbCO3) / CsSnCl3 as the light absorption layer is obtained by simulation design as described in step 4, and the transparent electrode is ITO with a thickness of 50nm.
[0067] Preferably, the photoelectric conversion efficiency of the perovskite solar cell with (PbSO4, PbCO3) / CsSnCl3 as the light absorption layer is obtained by simulation design as described in step 4, and the carrier recombination loss in the structure is represented by SRH recombination.
[0068] Compared with the prior art, the heterostructure construction method of the present invention is suitable for crystal materials of different crystal systems.
[0069] Compared with the prior art, the present invention realizes the construction of multilayer heterojunction structure crystal materials of different crystal systems, and characterizes the heterojunction structure materials based on density functional theory to analyze the performance of the heterojunction structure.
[0070] Compared with the prior art, the calculation method adopted by the present invention effectively combines modern technology, greatly reduces the experimental cost and time cost, and the process operation is simple and adjustable. BRIEF DESCRIPTION OF THE DRAWINGS
[0071] Figure 1 The passivation mechanism (left) and type II band structure (right) between the PbSO4 / SnCl and PbCO3 / SnCl interfaces of the embodiments of the present invention;
[0072] Figure 2 The electronic structures of CsSnCl3 (SnCl cross section), PbSO4 / SnCl, and PbCO3 / SnCl in the embodiments of the present invention;
[0073] Figure 3 (a) different orbitals and (c) partial wave density of states (PDOS) of each atom of PbSO4 / SnCl according to an embodiment of the present invention; (b) different orbitals and (d) PDOS of each atom of PbCO3 / SnCl;
[0074] Figure 4 The electron localization functions of (a) 3D and (c) 2D sections (along the c-axis) of PbSO4 / SnCl of the embodiment of the present invention; the electron localization functions of (b) 3D and (d) 2D sections (along the c-axis) of PbCO3 / SnCl;
[0075] Figure 5 The light absorption intensity of CsSnCl3, PbSO4 / SnCl, and PbCO3 / SnCl in the embodiments of the present invention;
[0076] Figure 6 is the photoconductivity curve of the (PbSO4 / PbCO3) / CsSnCl3 heterojunction of the embodiment of the present invention, Figure 6 -a is the imaginary conductivity (Im), Figure 6 -b is the real conductivity (Re);
[0077] Figure 7 1. The JV curve and energy level arrangement of the (PbSO4 / PbCO3) / CsSnCl3 perovskite solar cell device according to an embodiment of the present invention. DETAILED DESCRIPTION
[0078] The present invention is further described below with reference to the accompanying drawings and embodiments.
[0079] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specifically emphasized, all technical and scientific terms used herein have the same meanings as those commonly understood by ordinary technicians in the technical field to which the present application belongs.
[0080] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. The description of the term "some specific embodiments" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same implementation or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0081] This embodiment provides a design method for defect passivation of a perovskite absorption layer based on density functional theory, comprising the following steps:
[0082] Step s1: Set the unit cell parameters of CsSnCl3 according to the experimental values to construct a crystal structure model, use VASP software to perform structural relaxation optimization, obtain a stable CsSnCl3 unit cell, and select a suitable k point for electronic structure calculation;
[0083] Step s2: Set the unit cell parameters of PbSO4 and PbCO3 according to the experimental values to construct a crystal structure model, use VASP software to perform structural relaxation optimization, obtain the stable state of PbSO4 and PbCO3 primitive cells, select appropriate k points for electronic structure calculation, and obtain the bandgap width and band edge position of PbSO4, PbCO3 and CsSnCl3 perovskite materials;
[0084] Step s3: cutting the surfaces of PbSO4, PbCO3 and CsSnCl3 obtained in steps s1 and s2, combining PbSO4, PbCO3 and CsSnCl3 in sequence to construct a heterojunction structure, screening out a (PbSO4, PbCO3) / CsSnCl3 heterojunction structure with a stable interface through surface interface structure design, and performing structural relaxation optimization on the heterojunction structure to obtain a stable heterojunction structure;
[0085] Step s4: The final experimental performance values of the (PbSO4, PbCO3) / CsSnCl3 heterojunction are obtained through theoretical calculations and visualized characterization (including electron localization function, state density, band structure, differential charge density, light absorption rate, photoconductivity, and light refractive index), the passivation mechanism is explored, and the photoelectric conversion efficiency of the perovskite solar cell with (PbSO4, PbCO3) / CsSnCl3 as the light absorption layer is obtained through simulation design calculations.
[0086] In this embodiment, the specific content of constructing the CsSnCl3 crystal structure using MedeA software described in step s1 is: setting the size and space group of the unit cell according to the experimental values, and performing visualization operations.
[0087] In this embodiment, the specific content of using VASP software to optimize the structure of CsSnCl3 in step s1 to obtain a stable CsSnCl3 primitive cell is as follows: setting relevant restriction parameters for the constructed CsSnCl3 crystal structure, using the VASP module of MedeA software to optimize the structure based on the plane wave method density functional theory, and allowing the atomic position, unit cell volume and unit cell shape to be changed according to the interatomic interaction force during the crystal structure optimization process. The PBE functional of the generalized gradient approximation (GGA) is used to describe the exchange interaction between electrons.
[0088] In this embodiment, the method of setting the unit cell parameters of PbSO4 and PbCO3 according to experimental values to establish a crystal structure model in step s2 is the same as the method of step s1.
[0089] In this embodiment, the specific content of selecting a suitable k point to calculate the bandgap width and band edge position of PbSO4, PbCO3 and CsSnCl3 perovskite materials in step s2 is: using different k points to perform self-consistent calculations on the perovskite unit cell until the total energy of the PbSO4, PbCO3 and CsSnCl3 unit cell reaches a minimum value and does not change with the increase of the k point, and then selecting the k point for electronic structure calculation.
[0090] In this embodiment, the specific content of selecting a suitable k point to calculate the bandgap width and band edge position of PbSO4, PbCO3 and CsSnCl3 perovskite materials in step s2 is: the band edge position is calculated from the work function and the bandgap width.
[0091] In this embodiment, the surface of PbSO4, PbCO3 and CsSnCl3 is cut as described in step s3. Specifically, the MedeA software is used to cut the surface of the PbSO4, PbCO3 and CsSnCl3 crystal structures, and the crystal plane with the lowest surface energy is selected as the heterojunction bonding surface, and the structure of the cut surface structure is optimized as described above to obtain a stable cut surface structure.
[0092] In this embodiment, the surfaces of PbSO4, PbCO3 and CsSnCl3 are cut as described in step s3, and PbSO4, PbCO3 and CsSnCl3 are combined in sequence to construct a heterojunction structure. Specifically, CsSnCl3 can be cut into two different exposed surfaces in one direction, which are combined with PbSO4 and PbCO3 in sequence to form a heterojunction.
[0093] In this embodiment, in step s3, PbSO4, PbCO3 and CsSnCl3 are combined in sequence to construct a heterojunction structure, and the surface interface structure is designed. Specifically, the constructed (PbSO4, PbCO3) / CsSnCl3 heterojunction band structure can form a type II heterostructure.
[0094] In this embodiment, step s3 describes that PbSO4, PbCO3 and CsSnCl3 obtained in steps s1 and s2 are combined in sequence to construct a heterojunction structure, and the specific content of the surface interface structure design is as follows: the preliminary construction of the heterojunction is to use MedeA software to visualize the two cross-sectional structures, stack the cross-sectional surfaces of the geometric model, and construct a rough heterojunction geometric model. This structural model also needs to be optimized-adjusted parameters-optimized (the optimized structure is consistent with the above-mentioned optimization content of the monomer crystal structure) to obtain the required stable geometric structure.
[0095] In this embodiment, before constructing the heterojunction, the lattice mismatch degree of the two monomer surfaces at the c-direction interface of the heterojunction structure needs to be calculated, and the mismatch degree formula is as follows:
[0096] Δ=[(|a1-a2| / a1)-1]*100%
[0097] Where Δ represents the lattice mismatch of the monomer crystal structures on both sides of the heterojunction interface;
[0098] a1 represents the lattice constant in the a direction of the upper crystal structure of the heterojunction interface in the heterojunction;
[0099] a2 represents the lattice constant in the a direction of the lower crystal structure of the heterojunction interface in the heterojunction;
[0100] In this embodiment, before constructing the heterojunction, the angle mismatch of the two monomer surfaces at the c-direction interface of the heterojunction structure needs to be calculated. The mismatch formula is as follows:
[0101] η=(|γ1-γ2| / γ1)*100%
[0102] Where η represents the angular mismatch of the monomer crystal structures on both sides of the heterojunction interface;
[0103] γ1 represents the lattice angle size in the ab direction of the upper crystal structure of the heterojunction interface in the heterojunction;
[0104] γ2 represents the lattice angle size in the ab direction of the crystal structure under the heterojunction interface in the heterojunction;
[0105] It is worth noting that when constructing a geometric crystal structure model of a heterojunction material, in order to ensure the true reliability of the constructed structure and to ensure the stability of the structure, the mismatch rate must be ≤5%. In order to minimize the mismatch of the crystal lattice during construction, the crystal structure is usually expanded and the appropriate lowest common multiple is selected for expansion.
[0106] When constructing a heterostructure, it is necessary to set The vacuum layers on the left and right are intended to ensure that the heterojunction does not continue in the c direction, making it a separate multilayer structure. More importantly, it is intended to avoid the influence of other interaction forces on the interface structure.
[0107] In this embodiment, the structure optimization calculation is based on the VASP simulation software package of the plane wave method density functional theory; in the calculation process, based on the generalized gradient approximation (GGA), the PBE exchange correlation function description and the HSE06 hybrid density functional are used, and the plane wave cutoff energy is selected to follow the ENCUT≤ENMAX principle and the mechanical convergence standard is , the self-consistent convergence criterion is 10 -7 -10 -5 eV.
[0108] In this embodiment, the final experimental performance values of the (PbSO4, PbCO3) / CsSnCl3 heterojunction are obtained by theoretical calculation as described in step s4 and visualized and specifically characterized, and the specific content of the final performance parameters is as follows: the electronic structure, optical and electrical related parameters of the optimized heterojunction structure are calculated using the VASP module based on density functional theory to characterize the relevant performance of the heterogeneous crystalline structure.
[0109] In this embodiment, the optical properties of the heterogeneous crystalline structure are characterized by: the macroscopic optical constants of the solid are related to its microscopic band structure, transition matrix elements and state density; the imaginary part of the crystal dielectric constant ε2(ω) is obtained by calculating the transition of electrons between occupied orbits and unoccupied orbits; therefore, from the band structure, according to the direct transition probability definition and the Kramers-Kroning dispersion relation, the real part of the dielectric constant ε1(ω), the refractive index n(ω), the absorption coefficient α(ω), the conductivity σ(ω), the refractive index R(ω) and the extinction coefficient L(ω) of the solid can be calculated:
[0110] The electrical properties are characterized by the dielectric constant ε, which reflects the response of the medium to the external electric field. The formula of the dielectric function is as follows:
[0111] ε(ω)=ε1(ω)+iε2(ω)
[0112] ω is the optical frequency, ε1(ω) and ε2(ω) are the real and imaginary parts of the dielectric function, respectively, the imaginary part represents the absorption behavior and the real part is derived from the imaginary part [ε1(ω) and ε2(ω) are given in detail below].
[0113] Furthermore, electronic structure calculation is to determine the specific band structure and state density information by calculating the Mülliken population number of the system. The principle of optical calculation is to calculate the transition of electrons in the band gap. The calculation formula is as follows:
[0114]
[0115]
[0116]
[0117]
[0118] Among them, ε1(ω) and ε2(ω) are the calculation equations for the real and imaginary parts of the dielectric constant, n(ω) is the calculation equation for the refractive index, and R(ω) is the calculation equation for the reflectivity.
[0119] The optical performance characterization, in which the response degree of the structure to light is expressed according to the light absorption coefficient, is derived and calculated by the dielectric function to obtain the absorption spectrum. According to the Lambert-Beer law, a larger absorption coefficient leads to a larger absorption rate. The dielectric function ε and α absorption coefficients are calculated by the following formula:
[0120]
[0121] Among the optical properties, photoconductivity is the key information that can be used to determine the efficiency of the structure in converting photon energy absorbed. The calculation formula of photoconductivity is as follows:
[0122]
[0123] σ0=e 2 n e τ / m* is the DC conductivity, n e is the electron density, τ is the electron relaxation time, m* is the effective electron mass, and the parameter c = [-1, 0] represents the original velocity fraction of the electron after the collision, which is related to the electron localization effect. The real part (Re) of the photoconductivity corresponds to the actual energy consumption, and the imaginary part (Im) represents the conversion of the electric field energy to the electron kinetic energy, based on which it can provide key information on energy changes to reflect the photoelectric conversion efficiency.
[0124] Among the optical properties, the extinction coefficient is described by the following formula:
[0125]
[0126] Preferably, the heterostructure construction method described in this embodiment is suitable for combining crystal materials of different crystal systems.
[0127] Preferably, this embodiment realizes the construction of multi-layer heterojunction of crystal materials of different crystal systems.
[0128] Preferably, the heterojunction structure combined in this embodiment is calculated based on the density functional theory, and its performance can be analyzed in detail through specific characterization.
[0129] Preferably, the specific examples of this embodiment are as follows:
[0130] Step 1
[0131] The CsSnCl3 crystal structure was constructed using MedeA software, and the lattice parameters set were as follows: The space group is The CsSnCl3 structure was optimized using VASP software to obtain a stable CsSnCl3 unit cell. The specific optimization parameters were as follows: During the crystal structure optimization process, the atomic position, unit cell volume, and unit cell shape were allowed to change according to the interatomic interaction force. The PBE functional of the generalized gradient approximation (GGA) was used to describe the exchange interaction between electrons. The cutoff energy was set to 450 eV and the energy convergence value was 1×10 -6 eV, the force converges to After optimization, the stable CsSnCl3 structure is obtained. Due to the relaxation of the structure, its parameters are changed to:
[0132] Step 2
[0133] The crystal structures of PbSO4 and PbCO3 were constructed using MedeA software, and the lattice parameters set were as follows: The space groups are all Pnma. The PbSO4 and PbCO3 structures are optimized using VASP software to obtain stable PbSO4 and PbCO3 primitive cells. The specific optimization parameters are: During the crystal structure optimization process, the atomic position, unit cell volume and unit cell shape are allowed to change according to the interatomic interaction force. The PBE functional of the generalized gradient approximation (GGA) is used to describe the exchange interaction of electrons. The cutoff energy is set to 450 eV and the energy convergence value is 1×10 -6 eV, the convergence value of the force is Due to the structural relaxation and the crystallographic transformation of PbCO3, its parameters become:
[0134] Different k points are used to perform self-consistent calculations on the perovskite unit cell model until the total energy of the PbSO4, PbCO3 and CsSnCl3 units reaches the minimum value and does not change with the increase of the k point. Then the k point is selected for energy band calculation. The k point is sampled in the first Brillouin zone, with a sampling density of 6×6×6 and a sampling density of
[0135] Step 3
[0136] The (100)(001)(100) surface of the PbSO4, PbCO3 and CsSnCl3 crystal structures was cut and the k-point test band calculation was performed as mentioned above. It was found that the band edge positions of PbSO4, PbCO3 and CsSnCl3 were (-3.727eV, -6.299eV), (-3.554eV, -6.128eV) and (-4.279eV, -6.572eV), respectively, which can form the following Figure 1 The type II band structure shown.
[0137] MedeA was used to visualize the structure. By designing the surface interface structure, the mismatch matching of the PbSO4, PbCO3 and CsSnCl3 crystal structures was performed, and CsSnCl3 was expanded by 3×1. After optimization, the lattice parameters were obtained as follows: A 2×1×1 supercell was constructed for PbSO4, and the lattice parameters were optimized as follows: After the crystal vector transformation, PbCO3 becomes a 2×1×1 supercell, and the lattice parameters after optimization are:
[0138] The PbSO4 and CsSnCl3 crystal structures are constructed in the c direction as heterojunction structures, and the mismatch degree is calculated by the above mismatch degree calculation formula: CsSnCl3 crystal Therefore, the mismatch degree Δ(a)=1%, Δ(b)=3.8%, η(ɑ)=0, η(β)=0 is calculated, which meets the mismatch degree limit requirement.
[0139] The PbCO3 and CsSnCl3 crystal structures are constructed in the c direction as heterojunction structures, and the mismatch degree is calculated by the above mismatch degree calculation formula: CsSnCl3 crystal Therefore, the mismatch Δ(a)=1.7%, Δ(b)=4.7%, η(α)=0, η(β)=0 are calculated, which meets the mismatch limit requirement.
[0140] Combine PbSO4 / CsSnCl3 and PbCO3 / CsSnCl3 crystals according to the mismatch degree to construct a heterojunction structure with PbSO4 or PbCO3 crystals on the upper layer and CsSnCl3 crystals on the lower layer. The vacuum layer is formed, and the structure is optimized according to the above parameters to obtain stable PbSO4 / CsSnCl3 and PbCO3 / CsSnCl3 heterojunction structures.
[0141] Step 4
[0142] Using the density functional theory method, the HSE06 hybrid functional was used to calculate the band properties of the PbSO4 / CsSnCl3 and PbCO3 / CsSnCl3 heterojunction structures, and the GGA-PBE functional was used to calculate the state density of the structure, the localized distribution of electrons and visualize it, as well as the optical properties of the materials.
[0143] Figure 2The electronic structures of CsSnCl3 (SnCl cross section) (a), PbSO4 / SnCl (b), and PbCO3 / SnCl (c). It can be seen that the band gap of the CsSnCl3 perovskite heterojunction structure after passivation with PbSO4 and PbCO3 has shrunk significantly compared with the monomer CsSnCl3 perovskite, with a shrinkage range of 0.72-0.83 eV. This shrinkage can effectively expand the absorption range of the device structure for the solar spectrum, allowing it to obtain more energy under limited lighting conditions to facilitate the generation of photogenerated electrons and transitions.
[0144] The two cross-sections CsCl and SnCl obtained from CsSnCl3 were combined with PbSO4 / CsCl and PbCO3 for heterojunction, and the interface binding energy E of the four heterostructures was calculated. bin As shown in Table 1, it is obvious that the interface binding energies of the four heterostructures are all less than 0, indicating that the four interface structures can exist stably. The interface binding energy of PbSO4 / SnCl is much smaller than that of the other three heterostructures, and the interface of PbCO3 / SnCl is also more stable than that of PbSO4 / CsCl and PbCO3 / CsCl. PbSO4 / SnCl and PbCO3 / SnCl are further studied.
[0145] Table 1. Binding energy E of heterojunction interfaces binding
[0146]
[0147] like Figure 3 As shown, the DOS of the occupied state (valence band) of CsSnCl3 is mainly contributed by Cl-3p, and the empty state (conduction band) is mainly contributed by Sn-5p. The valence band of PbSO4 and PbCO3 is mainly composed of O-2p state, the conduction band is mainly Pb-5d, and the s state is not sensitive to the Fermi level. The PDOS of each atom shows ( Figure 3 c / d), the overlap between Cl-3p and O-2p orbitals is mainly at the top of the valence band, indicating that the photoexcited electrons are transferred from O-2p to the empty Cl-3p orbital. This causes the O atom to become a photovacancy site, while the Cl atom replaces the O atom to store the photoexcited electron. PbSO4 and PbCO3 are passivation layers inserted between the perovskite and the electron transport layer, and the energy difference between their atomic orbitals determines the charge transfer capacity of the interface. Orbital hybridization at the interface strongly affects the electronic properties and stability, which determines the strength of the absorption of sunlight.
[0148] By selecting atoms on both sides of the PbSO4 / CsSnCl3 and PbCO3 / CsSnCl3 interfaces for test calculations, the bonding mode between the interfaces and the possible chemical bonds are verified. The Bader data are given in Table 2 (PbSO4 / CsSnCl3) and Table 3 (PbCO3 / CsSnCl3).
[0149] From Table 2 and Table 3, we can see that for the PbSO4-SnCl interface, except for Sn-1 and O-9, the difference in charge change of the remaining atoms between the interfaces is small for the neutral state of the atoms. This can infer that there is basically no ionic bond at the heterojunction interface. For the Sn-1 and O-9 atoms with large numerical fluctuations, we speculate that due to the bonding of the exposed perovskite surface with the PbSO4 surface that constitutes the heterostructure, new chemical bonds are formed. This new chemical bond can effectively prevent the dangling bonds on the perovskite surface from being affected by water molecules or impurities in the air, reduce the self-decomposition of the perovskite, avoid the defects caused by it, and ensure the structural properties of the perovskite itself. Similar situations can also be observed at the PbCO3-SnCl interface. For the Sn-3 / O-14 atoms and the Sn-5 / O-26 atoms, charge exchanges with similar values appear. In addition, due to the formation of new bonds between the interfaces, the interfacial bonding stability of the two structures may be enhanced. Although the newly appeared bonds may cause the original lattice structure to deform, this is also the effect of the lattice energy relaxing itself to stabilize, and the deformation that occurs must be small.
[0150] Table 2. Bader charge of PbSO4 / CsSnCl3 heterojunction
[0151]
[0152] Table 3. Bader charge of PbCO3 / CsSnCl3 heterojunction
[0153]
[0154] The electron local density (ELF) calculations were performed on the two heterostructures. The results obtained by ELF calculations are as follows: Figure 4 It can be clearly observed that Sn-1 and O-9 at the heterojunction interface produce a strong localization effect, and the same is true for Sn-3 / O-14 and Sn-5 / O-26 atomic pairs. In addition, the spatial coordinates of each atom at the PbSO4 / CsSnCl3 interface have changed. The spatial coordinate shift of each atom at the PbCO3 / CsSnCl3 interface is relatively small, only This also shows that the formation of Sn-O bonds does lead to the distortion of the crystal structure, but fortunately, this distortion is extremely small and can be ignored. This also means that the introduction of PbSO4 and PbCO3 at the CsSnCl3 interface can significantly reduce the appearance of empty binding sites with unsaturated coordination on the CsSnCl3 surface, avoiding the combination with other impurities, thereby avoiding possible structural defects.
[0155] The light absorption spectra of the monomer perovskite and the heterojunction in two passivation states were obtained by calculation, such as Figure 5 It can be clearly seen that in the ultraviolet region (0-380nm), the light absorption intensity of the heterojunction structure after passivation with PbSO4 and PbCO3 is significantly improved compared with the monomer perovskite structure. In the visible light region, a change occurs at about 500nm. The light absorption intensity of the heterojunction structure passivated with PbCO3 is still the highest (0.897·10 5 cm -1 ), but PbSO4 / CsSnCl3 and monomer perovskite cross. After 500nm, the light absorption intensity of PbSO4 / CsSnCl3 is weaker than that of monomer perovskite. Interestingly, after 500nm, PbCO3 / CsSnCl3 and monomer perovskite show similar absorption curves, and the monomer perovskite has a significant left shift compared to PbCO3 / CsSnCl3, which indicates that the absorption intensity of PbCO3 / CsSnCl3 is significantly stronger than that of monomer perovskite. In the wavelength range of 500-1200nm, the light absorption intensity of PbSO4 / CsSnCl3 is weaker than that of monomer perovskite. The reason may be the lattice distortion caused by interface bonding. The atomic displacement of the PbCO3 / CsSnCl3 structure in the same wavelength range is only 1 / 4 of that of PbSO4 / CsSnCl3. In the range of 500-1200nm, the absorption curve of PbSO4 / CsSnCl3 is smaller than that of perovskite. Compared with the bare perovskite interface structure, its slight intensity drop is acceptable compared with the significant improvement in the stability of the structure. In the range of 0-1200nm, the heterojunction structure passivated by PbCO3 shows excellent light absorption intensity, which is worth noting. This can greatly improve the photoelectric conversion efficiency of the device under limited light conditions, and the passivated device structure can maintain a high environmental stability, greatly extending the working life of the device.
[0156] In order to more fully describe the optical properties of PbSO4 / SnCl, PbCO3 / SnCl and CsSnCl3, the photoconductivity ( Figure 6 ). The real part (Re) of the optical conductivity corresponds to the actual energy consumption, and the imaginary part (Im) represents the conversion of electric field energy into electron kinetic energy. Based on this fact, it can provide key information on energy changes to predict optical properties. Figure 6 -a(Im) shows that PbSO4 / SnCl exhibits higher conductivity in the visible region (380-780nm, blue region), while the conductivity of PbCO3 / SnCl is not as good as that of PbSO4 / SnCl, but still higher than that of CsSnCl3. Figure 6 -b(Re), PbSO4 / SnCl and PbCO3 / SnCl show higher peaks and smoother curves, which is due to the improved structural stability. The above analysis shows that the modification and passivation of PbSO4 / SnCl and PbCO3 can significantly improve the photoconductivity of CsSnCl3, thereby further improving the PCE of perovskite solar cells.
[0157] Table 4 shows the parameters of each layer of the two designed perovskite solar cells
[0158] Table 4. Parameters of each layer in perovskite solar cells with (PbSO4 / PbCO3) / CsSnCl3 as active layer
[0159]
[0160] Energy level arrangement and JV curve of (PbSO4 / PbCO3) / CsSnCl3 perovskite solar cell device Figure 7 As shown, Figure 7 -c / d can be seen to form a type II band structure with good energy level arrangement. Figure 7 -a / b shows that the short-circuit current density of PbSO4 / CsSnCl3 as the light absorption layer is 21.6821mA / cm 2 , open circuit voltage 0.909V, fill factor 77.0947%, the final conversion efficiency is 15.1946%. For PbCO3 / CsSnCl3 as the light absorption layer, the short circuit current density is basically the same, which is 21.6822mA / em 2 , but the open circuit voltage increased significantly by about 9%, reaching 0.993V, the fill factor was 80.7154%, and the actual conversion efficiency was 17.3783%. A good improvement. The above embodiments and results show that the interface modification and passivation of the CsSnCl3 perovskite light absorption layer by PbSO4 and PbCO3 can significantly improve the performance of CsSnCl3 and further improve the photoelectric conversion efficiency of perovskite solar cells. PSCs passivated with PbCO3 showed higher photoelectric conversion efficiency.
[0161] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A design method for defect passivation of perovskite absorption layer based on density functional theory, characterized in that: The steps include: Step s1: Set the unit cell parameters of CsSnCl3 according to the experimental values to construct a crystal structure model, use VASP software to perform structural relaxation optimization, obtain a stable CsSnCl3 unit cell, and select a suitable k point for electronic structure calculation; Step s2: Set the unit cell parameters of PbSO4 and PbCO3 according to the experimental values to construct a crystal structure model, use VASP software to perform structural relaxation optimization, obtain the stable state of PbSO4 and PbCO3 primitive cells, select appropriate k points for electronic structure calculation, and obtain the bandgap width and band edge position of PbSO4, PbCO3 and CsSnCl3 perovskite materials; Step s3: cutting the surfaces of PbSO4, PbCO3 and CsSnCl3 obtained in steps s1 and s2, combining PbSO4, PbCO3 and CsSnCl3 in sequence to construct a heterojunction structure, screening out a (PbSO4, PbCO3) / CsSnCl3 heterojunction structure with a stable interface through surface interface structure design, and performing structural relaxation optimization on the heterojunction structure to obtain a stable heterojunction structure; Step s4: The final experimental performance values of the (PbSO4, PbCO3) / CsSnCl3 heterojunction are obtained through theoretical calculations and visualized characterization (including electron localization function, state density, band structure, differential charge density, light absorption rate, photoconductivity, and light refractive index), the passivation mechanism is explored, and the photoelectric conversion efficiency of the perovskite solar cell with (PbSO4, PbCO3) / CsSnCl3 as the light absorption layer is obtained through simulation design calculations.
2. A design method for defect passivation of perovskite absorption layer based on density functional theory, characterized in that: In steps s1, s2, and s3, the stable state of CsSnCl3, PbSO4, PbCO3 unit cells and (PbSO4, PbCO3) / CsSnCl3 heterojunction structure means that the energy of CsSnCl3, PbSO4, PbCO3 unit cells and (PbSO4, PbCO3) / CsSnCl3 heterojunction structure reaches the minimum value.
3. A design method for defect passivation of perovskite absorption layer based on density functional theory, characterized in that: In steps s1 and s2, the selecting of a suitable k point for electronic structure calculation includes: using different k points to perform self-consistent calculations on the structural primitive cell until the total energy of the structural primitive cell reaches a minimum value and does not change with the increase of the k point, and then selecting the k point for electronic structure calculation.
4. A design method for defect passivation of perovskite absorption layer based on density functional theory, characterized in that: In steps s1, s2, and s3, the specific parameters for optimizing the crystal structure are obtained from the pseudopotential output file, specifically, the energy convergence value is 1×10 -6 eV, the convergence value of the force is The cutoff energy is 450 eV, the k point is sampled in the first Brillouin zone, the sampling points are 6×6×6, and the sampling density is To achieve lower error and stable crystal structure.
5. A design method for defect passivation of perovskite absorption layer based on density functional theory, characterized in that: In steps s1, s2, and s3, the density functional used in the structural relaxation optimization calculation is the PBE density functional, and the density functional used in the electronic structure calculation is the HSE06 hybrid density functional.
6. A design method for defect passivation of perovskite absorption layer based on density functional theory, characterized in that: In step s3, the surfaces of PbSO4, PbCO3 and CsSnCl3 are cut, and the cut surfaces are the crystal planes with the lowest surface energy, namely, PbSO4 (100), PbCO3 (001) and CsSnCl3 (100) planes. Combining PbSO4, PbCO3 and CsSnCl3 in sequence to construct a heterojunction structure must satisfy the requirements of "the lattice mismatch rate between the two interfaces is ≤5%, and the interlayer interface spacing is within the spacing of the interatomic force" within the scope".
7. A design method for defect passivation of perovskite absorption layer based on density functional theory, characterized in that: In step s3, the interface structure is designed to screen out the interface-stable (PbSO4, PbCO3) / CsSnCl3 heterojunction structure, where PbSO4 is a 2×1×1 supercell, PbCO3 is a 2×1×1 supercell after crystal vector transformation, and CsSnCl3 is a 3×1×1 supercell. The screening conditions are the degree of interface energy level matching (able to form a type II band structure) and the interface binding energy.
8. A design method for defect passivation of perovskite absorption layer based on density functional theory, characterized in that: In step s3, PbSO4, PbCO3 and CsSnCl3 are combined in sequence to construct a heterojunction structure. By designing the surface interface structure, a 15A vacuum layer is set in the vertical direction of the heterojunction interface (001) to avoid the influence of other interaction forces on the interface structure.
9. A design method for defect passivation of perovskite absorption layer based on density functional theory, characterized in that: In step s4, the photoelectric conversion efficiency of the perovskite solar cell with (PbSO4, PbCO3) / CsSnCl3 as the light absorption layer is obtained by simulation design calculation. PbSO4 / CsSnCl3 and PbCO3 / CsSnCl3 are used as the light absorption layer of the perovskite solar cell respectively, and the same external parameters are set to explore the changes in photoelectric performance.
Citation Information
Cited By
Theoretical design method of halide solid electrolyte
CN121439028A